The Contribution of the Language, Culture and Vision Constructed by Quran and Sunnah to the World Peace - Demirel, Serdar; K?l?ç, Zeynep Havva (IIUC Studies, 2014)
Many factors bring people together and unite them. Although these factors may have common characteristics in different civilizations and religions, they also have varying attributes. Today, Muslims need a consolidating language, not a divisive one. This is possible only when Muslims have a common language, culture and edifice constructed by revelation. This is crucial for the world peace. Because if peace cannot be achieved in the Muslim world and ethnic problems continue, it will, obviously, threaten regional and global peace. This article is about how Islam provided its followers a common language, culture and edifice constructed by revelation in theory and practice to unite them. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20410 IIUC Studies Vol.8 December 2011: 141-160